A THERMODYNAMIC DESCRIPTION OF METASTABLE C-TIALZRN COATINGS WITH TRIPLE SPINODALLY DECOMPOSED DOMAINS - Zhou, Jingjing; Zhang, Lijun; Chen, Li; Du, Yong; Liu, Zi-Kui (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
A critical thermodynamic assessment of the metastable c-TiAlZrN coatings, which are reported to spinodally decompose into triple domains, i.e., c-TiN, c-AlN, and c-ZrN, was performed via the CALculation of PHAse Diagram (CALPHAD) technique based on the limited experimental data as well as the first-principles computed free energies. The metastable c-TiAlZrN coatings were modeled as a pseudo-ternary phase consisting of c-TiN, c-AlN and c-ZrN species, and described using the substitutional solution model. The thermodynamic descriptions for the three boundary binaries were directly taken from either the CALPHAD assessment or the first-principles results available in the literature except for a re-adjustment of the pseudo-binary c-AlN/c-ZrN system based on the experimental phase equilibria in the pseudo-ternary system. The good agreement between the calculated phase equilibria and the experimental data over the wide temperature range was obtained, validating the reliability of the presently obtained thermodynamic descriptions for the c-TiAlZrN system. Based on the present thermodynamic description, different phase diagrams and thermodynamic properties can be easily predicted. It is anticipated that the present thermodynamic description of the metastable c-TiAlZrN coatings can serve as the important input for the later quantitative description of the microstructure evolution during service life.